2021
DOI: 10.4028/www.scientific.net/jnanor.66.85
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Active Carbon Nanoparticles with Improved Dispersivity in Water and Potential Application in Lymphatic Targeted Therapy of Colorectal Cancer

Abstract: A series of PEGylated active carbon nanoparticles were fabricated with improved dispersity in water and were explored for their ability for carrying drugs and potential application in lymphatic targeted tracing and chemotherapy of colorectal cancer. The active carbon nanoparticles were oxidized in a mild condition with 30% H2O2 solution and then mPEG-NH2 was grafted to the nanoparticles. Compared with the original carbon nanoparticles, the oxidized and PEGylated nanoparticles all present improved stability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…As a commercial material widely used in blood-contact fields, 52,53 Pellethane 2363-80AE (80AE) was used as a control. PEG is often used for surface modification to reduce the adhesion and activation of platelets for blood-contact materials, [54][55][56] thus PEG-based PU (PEGPU) was synthesized according to our reported method 14 as another control in our study (detailed information of PEGPU is shown in Table S4, ESI †). The results showed that the number of platelets adhered to the surface of TAPU1020 was slightly lower than that of 80AE.…”
Section: Hemocompatibilitymentioning
confidence: 99%
“…As a commercial material widely used in blood-contact fields, 52,53 Pellethane 2363-80AE (80AE) was used as a control. PEG is often used for surface modification to reduce the adhesion and activation of platelets for blood-contact materials, [54][55][56] thus PEG-based PU (PEGPU) was synthesized according to our reported method 14 as another control in our study (detailed information of PEGPU is shown in Table S4, ESI †). The results showed that the number of platelets adhered to the surface of TAPU1020 was slightly lower than that of 80AE.…”
Section: Hemocompatibilitymentioning
confidence: 99%